Synthesis, characterization and antimicrobial activities of triorganotin(IV) complexes with azo-azomethine carboxylate ligands: crystal structure of a tributyltin(IV) and a trimethyltin(IV) complex. Issue 2 (17th January 2017) - Singh, Keisham Surjit; Roy, Manojit; Roy, Subhadip; Ghosh, Bikash; Devi, N. Manglembi; Singh, Ch. Brajakishor; Mun, Lo Kong
Abstract: Triorganotin(IV) complexes with polyaromatic azo-azomethine carboxylate ligands viz . 2-{4-hydroxy-3-[(2/4-hydroxyphenylimino)methyl]phenylazo}benzoic acids [H3 L 1 /H3 L 2 ] were synthesized by reacting the ligands with either bis -tri- n -butyltin(IV) oxide (for1 and4 ) or trimethyltin(IV) chloride in presence of triethylamine (for2 and5 ) or triphenyltin(IV) hydroxide (for3 and6 ). The complexes were characterized by elemental analysis, UV, IR, NMR, and mass spectrometry. NMR spectroscopic studies of the compounds suggested that the complexes adopt four-coordinate tetrahedral geometry around tin in solution. Molecular structures of1 and2 were determined by single-crystal X-ray diffraction. Both complexes have distorted trigonal bipyramidal geometry around tin in the solid state. Compound1 is a one-dimensional (1-D) double chain coordination polymer which can be described as two different 24- and 30-membered non-porous macrocyclic rings constructed from two tributyltin units and two ligand moieties. The structure of2 comprises a discrete cyclic centrosymmetric dimer with two lattice water molecules per formula unit. In the dimer, two trimethyltin entities are bridged by two ligand moieties. The dimers are further interconnected with lattice water molecules by multiple O–H⋯O hydrogen bonds to form a 1-D H-bonded network. The complexes were also screened for their antimicrobial activities. Abstract :